Adjustment lending revisited : policies to restore growth - Corbo, Vittorio; Fischer, Stanley; Webb, Steven Benjamin (Washington, D.C. : World Bank, 1992)
This volume emerged from a symposium that was organized to present and discuss the background research for one such review. Part I examines how adjustment programs have affected growth, trade, and poverty in the medium term and what experience has taught about designing these programs. Part II deals with the Microeconomic foundations for sustainable growth-low inflation and increase investment, saving, and efficiency- which underlay successful adjustment. Part III brings together the issues to suggest adjustment strategies for the 1990s.
Includes bibliographical references.
hza 28/01/2019
Loans
Keywords: Loans, Foreign; Structural adjustment (Economic policy)